Concentrations of phthalates in bottled water under common storage conditions: Do they pose a health risk to children?. (March 2015) - Jeddi, Maryam Zare; Rastkari, Noushin; Ahmadkhaniha, Reza; Yunesian, Masud
Abstract: Of recent concern is the migration of phthalates from plastic products such as Polyethylene Terephthalate (PET) bottles into the water contain. These concerns should be addressed, especially considering the steady growth of the consumption of bottled water and the toxicological effects of phthalates. In this regard, special attention should be paid to children's consumption because of their particular susceptibility to the effects of phthalates. The aim of this study was to determine the concentrations of phthalates, including dibutyl phthalate (DBP), butyl benzyl phthalate (BBP) and bis(2-ethylhexyl) phthalate (DEHP), in bottled water and to estimate the health risk of endocrine disrupting chemicals due to water intake in children for the first time. Migration of phthalates was investigated in PET-bottled water under various storage conditions using gas chromatography–mass spectroscopy. A phthalate exposure assessment was performed to characterize their risk to the children's health via a calculated hazard quotient (HQ). It seems that increase in the temperature and the duration of storage affect phthalate migration, but the level of DEHP in bottled water was always very low and does not exceed 26.83% of the U.S. EPA maximum concentration limit (MCL). In particular, phthalate migration was not substantial at low temperatures (< 25 °C) and freezing conditions and the most abundant phthalate (DEHP) was not more than 10.6% MCL. The estimated child intake ranged from 0.01 μg/kg/day for BBP to 0.24 μg/kg/day for DEHP. Estimated phthalate intakes are generally in the safe range and exposure decreased with increasing age. Toxicological risk assessment of the maximum concentrations measured revealed a maximum HQ of 0.012 in the worst condition. Furthermore, a negligible carcinogenic risk of 6.5 × 10 − 7 for DEHP was observed. Consequently, risk evaluation showed that bottled water is safe for consumption by children. Highlights: Phthalate migration was not substantial at low temperatures and freezing conditions. Bottled water does not represent a relevant ingestion source of phthalates. The estimated exposure to endocrine disruptor phthalates via consumption of bottled water was extremely low. The carcinogenic risk by the highest concentration of DEHP in bottled water was negligible. PET-bottled water was found safe for consumption.